Reciprocal regulation of mir-10b, aurora-a, p53, and e-cadherin in cisplatin resistance and cell invasion of lung cancer: mir-10b-aurora-a axis in lung cancer malignancy - Lin, Chen-Chu; Wu, Chun-Chi (Cellular and Molecular Biology, 2025)
Lung cancer remains a leading cause of cancer-related deaths in developed nations, including Taiwan, mainly due to drug resistance or malignant conditions such as metastasis. Abnormal expression levels of oncogenes or tumor suppressors are recognized as inducing changes and malignancy in various cancers, including lung cancer. This report illustrates that mir-10b, Aurora-A, N-cadherin, and vimentin expression levels are elevated. At the same time, p53 and E-cadherin are reduced in A549cisR clones compared to parental cells, indicating a possible regulatory network among these molecules in malignant neoplasms. A functional assay demonstrated that the reduction of mir-10b or Aurora-A lessened both the resistance to cisplatin and cell motility of A549cisR cells, accompanied by a decrease in vimentin and N-cadherin, while an increase in p53 and E-cadherin. The co-expression of mir-10b agomir restores the drug-resistant and invasive motility of Aurora- A-knockdown A549cisR cells. Besides, ectopic expression of the active form of Aurora-A also increases mir-10b, N-cadherin, and vimentin expressions while decreasing E-cadherin and p53 levels, thus restoring cisplatin resistance and cell motility in mir-10b-knockdown A549cisR cells. Interestingly. Ectopic expression of E-cadherin reduced both motility and resistance to chemotherapeutic drugs, accompanied by altering Aurora-A, p53, and mir-10b levels in A549cisR cells. Subsequent investigations revealed that mir-10b secretion increased in A549cisR cells. Parental A549 cells cultured with a conditioned medium of A549cisR cells showed significantly reduced endogenous p53 expression, while inducing Aurora-A expression and increased viability after cisplatin treatment. Transfection with mir-10b antagomir reversed the expressions of Aurora- A, N-cadherin, vimentin, p53 and E-cadherin and the effects in parental A549 cells cultured in a conditioned medium. These findings suggest that the mir-10b-Aurora-A-E-cadherin pathway is crucial in orchestrating various malignancies, such as invasive motility and drug resistance, offering a possible malignancy-priming route in lung tumor cells with regular cisplatin treatment.